Field notes contributed by Tom Staudt, spring 1985 - Staudt, Thomas J.et al (1985)
Field notes contributed by Tom Staudt listing various bird sightings by himself and others, primarily in Johnson County. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly Report of spring 1985. Epson - sheet feed